Thinking, language and learning in initial teacher education - Taylor, Nick (Faculty of Education, University of the Free State, 2016)
Initial teacher education (ITE) serves as a bridge between prospective teachers exiting the school system to enrol in teacher education faculties, on the one hand and newly qualified teachers (NQTs) who are embarking on a career in schooling on the other. The present paper describes the language and thinking skills student teachers bring to their ITE programmes and the conditions faced by NQTs when they enter schools on the other side of the chalk face. This is the context within which we ask the question: To what extent are the universities providing the teachers required by the school system? While a review of the literature, together with new evidence emerging from the Initial Teacher Education Research Project (ITERP) study, indicates that the answer to this question is by no means unequivocally positive, the Department of Higher Education and Training (DHET) has issued new regulations aimed at addressing the gap between current programmes and the demands of schooling. We conclude by arguing that the quality of ITE will only be improved once teacher educators move their practices closer to those of practitioners in the strong professions, which are characterised by the development of a strong theoretical knowledge base, from which effective protocols of practice may be derived and which is continuously interrogated by the practitioners themselves. We suggest that the place to start on this quest is the instruction of prospective primary school teachers in early literacy and numeracy.
Keywords: Pre-service teacher education; Knowledge for teachers; Inferencing skills; Professional knowledge